Taking the Perspective of Others: Teaching about Racial Inequality* - Rich, Meghan; Andersen, Margaret (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We describe two exercises that teach students about two themes in the sociology of race: (1) the significance of racial symbols in constructing how people think about and experience race; and, (2) the cumulative and structural basis of racial inequality. The two exercises, one on the use of Native American mascots in school sports teams and one on the issues surrounding racial reparations, ask students to step outside of their own perspective (sometimes taking on views different from their own) and to present coherent argumentssupporting the view they are assigned to. Asking students to take on different viewpoints, with multiple viewpointsrepresented in the class on one issue, is a teaching tool thathelps students understand racial issues that are often complicated, emotional, and controversial.